Assessment of strategic healthcare purchasing and financial autonomy in Tanzania: the case of results-based financing and health basket fund - John Maiba; Neha S. Singh; Rachel Cassidy; Rachel Cassidy; Gemini Mtei; Josephine Borghi; Ntuli A. Kapologwe; Peter Binyaruka (Frontiers in Public Health, 2024)
BackgroundLow-and middle-income countries (LMICs) are implementing health financing reforms toward Universal Health Coverage (UHC). In Tanzania direct health facility financing of health basket funds (DHFF-HBF) scheme was introduced in 2017/18, while the results-based financing (RBF) scheme was introduced in 2016. The DHFF-HBF involves a direct transfer of pooled donor funds (Health Basket Funds, HBF) from the central government to public primary healthcare-PHC (including a few selected non-public PHC with a service agreement) facilities bank accounts, while the RBF involves paying providers based on pre-defined performance indicators or targets in PHC facilities. We consider whether these two reforms align with strategic healthcare purchasing principles by describing and comparing their purchasing arrangements and associated financial autonomy.MethodsWe used document review and qualitative methods. Key policy documents and articles related to strategic purchasing and financial autonomy were reviewed. In-depth interviews were conducted with health managers and providers (n = 31) from 25 public facilities, health managers (n = 4) in the Mwanza region (implementing DHFF-HBF and RBF), and national-level stakeholders (n = 2). In this paper, we describe and compare DHFF-HBF and RBF in terms of four functions of strategic purchasing (benefit specification, contracting, payment method, and performance monitoring), but also compare the degree of purchaser-provider split and financial autonomy. Interviews were recorded, transcribed verbatim, and analyzed using a thematic framework approach.ResultsThe RBF paid facilities based on 17 health services and 18 groups of quality indicators, whilst the DHFF-HBF payment accounts for performance on two quality indicators, six service indicators, distance from district headquarters, and population catchment size. Both schemes purchased services from PHC facilities (dispensaries, health centers, and district hospitals). RBF uses a fee-for-service payment adjusted by the quality of care score method adjusted by quality of care score, while the DHFF-HBF scheme uses a formula-based capitation payment method with adjustors. Unlike DHFF-HBF which relies on an annual general auditing process, the RBF involved more detailed and intensive performance monitoring including data before verification prior to payment across all facilities on a quarterly basis. RBF scheme had a clear purchaser-provider split arrangement compared to a partial arrangement under the DHFF-HBF scheme. Study participants reported that the RBF scheme provided more autonomy on spending facility funds, while the DHFF-HBF scheme was less flexible due to a budget ceiling on specific spending items.ConclusionBoth RBF and DHFF-HBF considered most of the strategic healthcare purchasing principles, but further efforts are needed to strengthen the alignment towards UHC. This may include further strengthening the data verification process and spending autonomy for DHFF-HBF, although it is important to contain costs associated with verification and ensuring public financial management around spending autonomy.